(untitled) (El Hilo de la Fabula, 2023)
María Rosa Lojo analyzes here the different kinds of transoceanic trips accomplished by the feminine characters in her books. Politician women, intellectuals, artists, or just ordinary women; exiled, migrant or tourist women who explore another reality, they are always in some way foreigners within a world managed by men, which they look at from another perspective. Manuela Rosas, Eduarda Mansilla, Victoria Ocampo, are some of the historical characters recreated in these novels, along with other wholly fictional women characters. In them the bravery needed to make the leap towards the other side without losing one’s memory is reunited with the continuity of a creative women’s legacy.